Geopolitics of the Belt and Road Initiative: Implications for Myanmar - Thaingi Khin Htwe (UNIVERSITAS PEMBANGUNAN NASIONAL VETERAN JAWA TIMUR, 2020)
This article aims to examine the implications of China’s Belt and Road Initiative (BRI) for Myanmar. BRI is an economic and strategic agenda of China. Because of its strategic geographical location, Myanmar becomes an important area of China in implementing its BRI projects. Beijing has raised the multi-level engagement in Myanmar such as economic and infrastructure cooperation; provide assist for the government’s peace process, and stand at Myanmar’s side in the international community. Therefore, BRI could have implications for Myanmar. This research answers the following questions: what are the implications of China’s Belt and Road Initiative for Myanmar; why Myanmar is important for China and how will Myanmar benefit from China’s BRI.